PENERAPAN PENDEKATAN STEM DALAM PEMBELAJARAN SENI UNTUK MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR DI SEKOLAH INDONESIA MAKKAH - rahmawati, siti; Hartono, Hartono; Rokhman, Fathur; Wagiran, Wagiran (JUSEDA, 2024)
Art learning plays an important role in fostering students' creativity, especially at the elementary school level. In the era of modern education, the STEM (Science, Technology, Engineering, Mathematics) approach has been applied in various disciplines, including art, to provide a richer learning experience. This study explores the application of the STEM approach in art learning at Sekolah Indonesia Makkah and its impact on students' creativity. The methods used include qualitative and quantitative with observations, interviews, and questionnaires given to teachers and students. The results show that the application of the STEM approach can significantly improve aspects of student creativity, especially in the elements of originality, flexibility, and fluency of ideas. These findings are evidence that the STEM interdisciplinary approach can help meet the needs of innovative learning in a multicultural educational environment.